Finding Harmony in Academic Interactions: Toward Transformative Theological Learning in Christian Higher Education - Daniel Ginting; Ratri Kusuma Wijaya (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2026)
This study examines the relationship between lecturers’ ego-state typologies and student satisfaction at a theological college in Malang, Indonesia. Employing a descriptive correlational design, the research involved nine lecturers and sixty students, using quantitative questionnaires to identify lecturers’ ego states (Parent, Adult, Child) and assess student satisfaction. Findings reveal a convergence of perceptions between lecturers and students, with the Nurturing Parent and Adult ego states predominating. Lecturers who demonstrate empathy, support, and rationality enhance students’ comfort and satisfaction, whereas overly authoritarian or excessively compliant behaviors prove less effective. The results underscore the importance of balancing empathy, rationality, and spiritual modeling to strengthen academic interactions, foster a positive learning environment, and support students’ intellectual and spiritual development.